Clinical characteristics and prognostic analysis of patients with type 2 diabetic kidney disease and non-diabetic kidney disease - Yu, Can; Shi, Wen; Chen, Enhui; Qiu, Yang; Gao, Li; Fang, Hansheng; Ni, Jun; Yu, Dongrong; Jin, De (Frontiers in Endocrinology, 2025)
BackgroundIn diabetic patients, non-diabetic kidney disease (NDKD) may occur independently or alongside diabetic kidney disease (DKD). This study explored the utility of kidney biopsy in type 2 diabetes mellitus (T2DM) patients and the predictability of diagnosing DKD combined with NDKD using clinical and laboratory data.MethodsThis retrospective study examines medical records of T2DM patients who underwent percutaneous renal biopsy at Hangzhou TCM Hospital, Zhejiang Chinese Medical University, from 2012 to 2023. The patient’s demographic, clinical, blood test and pathological examination data were retrieved from their medical records. Multivariate regression analysis evaluated predictive factors for NDKD superimposed on DKD (DKD+NDKD).ResultsA total of 285 patients were analyzed. The average age at the time of renal biopsy was 53.26 ± 10.55 years. The duration of diabetes was 93.19 ± 70.78 months. Of the patient population, 35.44% (101/285) were diagnosed with DKD alone, while 64.56% (184/285) had DKD+NDKD. Immunoglobulin A nephropathy was the most common pathological type in the DKD+NDKD group, accounting for 37.30% of the patients. Cystatin C [HR=2.688, 95% CI 1.035-6.879, P < 0.05] independently predicted the prognosis of patients with DKD+NDKD.ConclusionsThese findings suggest that cystatin C plays a role in influencing the prognosis of patients with DKD + NDKD, indicating that NDKD patients might require distinct treatment strategies compared to those with DKD alone. However, further prospective clinical trials are needed to provide more clarity on the prognosis and outcomes of diabetic patients.